Kinematic gait analysis in children with valgus deformity of the hindfoot - Svoboda, Zdenek; Honzikova, Lucie; Janura, Miroslav; Vidal, Tabata; Martinaskova, Eliska (Acta of Bioengineering and Biomechanics, 2014)
Deformities of the feet in children can influence not only optimal foot development but also the development of other body segments. The aim of the study was to compare the hip and pelvis kinematics in groups of children with and without valgus deformity of the hindfoot. Three groups of children participated in the study: bilateral hindfoot valgosity (11 children, age 5.4 ± 1.4 years), unilateral hindfoot valgosity (14 children, age 5.6 ± 1.6 years) and the control group (8 children, 4.8 ± 1.2). Hindfoot valgus angle was measured clinically during standing. Hindfoot valgosity was considered in the range of 6 to 20 degrees. Kinematic data from five trials for each child was obtained using the Vicon MX system (six infrared cameras, frequency 200 Hz, Vicon Motion Systems, Oxford, UK). The results of our study showed significantly higher pelvic anteversion during the whole gait cycle for both unilateral and bilateral hindfoot valgosity children and significantly higher hip external rotation during the first half of the stance phase in bilateral deformity. The differences in the hip and pelvis kinematics, when compared to the control group, are higher for the group with bilateral deformity than in the group with unilateral deformity.
Keywords: Female; kyčelní kloub; dítě; předškolní dítě; Gait; ženské pohlaví; Reproducibility of Results; lidé; Sensitivity and Specificity; senzitivita a specificita; Flatfoot; Range of Motion, Articular; plochá noha; reprodukovatelnost výsledků; rozsah kloubních pohybů; Hip Joint; Male; Walking; Child, Preschool; coxa valga; Ankle Joint; Child; Coxa Valga; mužské pohlaví; chůze (způsob); chůze; hlezenní kloub; Humans